Parenting Characteristics among Adults With Social Anxiety and their Influence on Social Anxiety Development in Children: A Brief Integrative Review - Garcia, Katelyn M.; Carlton, Corinne N.; Richey, John A. (Frontiers in Psychiatry, 2021)
The purposes of this brief integrative review are to identify and critically evaluate recent work in the area of parenting processes that are disproportionately observed among parents with social anxiety disorder (SAD) that may ultimately increase risk among offspring, and to further link these processes to specific targets for intervention. Accordingly, we first evaluate the relevance of specific parenting styles as they pertain to increased risk of developing SAD among offspring. Second, we link these parenting processes to observations of certain unfavorable consequences among socially anxious youth, such as low perceived autonomy and poorer social skills. Finally, in light of these consequences we extend our conclusions into potentially modifiable targets among parents with SAD, focusing on the enhancement of autonomy and facilitating offspring’s normative period of transition into independence during adolescence. Overall, we conclude that parenting behaviors commonly observed among adults with SAD such as overcontrol and low parental warmth, likely have a direct impact on the development of social anxiety symptoms among their children. However, these parenting behaviors are plausibly modifiable and therefore repurposing existing interventions for use among parents with SAD in conjunction with interventions with their offspring is likely to provide direct clinical benefit.